Role of Service Personnel Nurse in Implementation of Electronic Medical Records to Improve Inpatient Services at Adventist Hospital Bandung - Nora Naibaho; Sri Sundari; Bahana Wiradanti; Marisi Pakpahan; Freddy J. Rumambi (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
Electronic Medical Record (EMR) is a technology-based information system created to improve health services, where this system helps medical personnel in providing services faster and more accurately, but in its implementation, the technology system takes time to adapt, therefore it is important for hospitals to continue to evaluate how the process of using EMR in the service delivery process. This study aims to determine the benefits, obstacles, and strategies used to optimize the implementation of EMR in the Inpatient Installation of Advent Hospital Bandung. This study uses a qualitative method to analyze phenomena related to the implementation of EMR in the Inpatient Installation of Advent Hospital Bandung, data collection was carried out by interviewing 9 informants who then processed the interview data and presented in narrative form. From this study it was found that EMR speeds up the work of nurses and is more accurate, but in its implementation informants complained about too many EMR features and nursing care with the same nursing diagnosis repeated on each shift so that a lot of time was wasted. In addition, technical problems such as wifi and electricity also often interfere with the work of nurses. From the interview with the informants, it was stated that the strategy to optimize the implementation of EMR in the Inpatient Installation of Adventist Hospital Bandung includes management, staff training, and technology infrastructure, in addition, nurse compliance is also considered to be an important key in optimizing the implementation of EMR. EMR can help nurses work better but still needs to develop simpler features that cover all the important aspects needed, as well as a mature strategy in optimizing the use of EMR in the Inpatient Installation of Adventist Hospital Bandung.